0579 Feasibility and Accuracy of Home-Based Sleep Studies among Blacks at Risk for Sleep Apnea: A Scoping Review. (27th April 2018) - Iqbal, R; Seixas, A; Chery, K; Tan, N; Sanchez, L; Jean-Louis, G
Abstract: Introduction: Although Blacks are at elevated risk for sleep apnea, the true prevalence of sleep apnea may be suppressed because of low participation in sleep assessment. Compared to polysomnography (PSG), home-based sleep studies may increase sleep apnea assessment rates. The aim of this scoping review is to provide an overview of the utility of portable monitoring (PM) devices in home-based studies among Blacks. Methods: We conducted a scoping review to investigate feasibility and accuracy of home-based sleep studies among Blacks. We searched for key terms such as "Portable Monitoring Devices" and "Sleep Apnea" within the MEDLINE, CINAHL and ScienceDirect database for articles published between January 1990 and December 2017. Articles were then screened for inclusion of portable sleep monitoring data of Black participants. Outcomes of interest included preference rate and accuracy of sleep devices compared to PSG. Results: Fifteen studies met our inclusion criteria. A total of ten different portable sleep monitoring devices were used. The most prominent device was the ApneaLink Plus (ResMed), which had a preference rate of 87% compared to Watch-PAT 200 preference rate of 82%. Participants rated the ApneaLink Plus monitor as very easy to use (median score, 2.5) on a 10-point Likert scale. Furthermore, studies have shown the ApneaLink Plus has a sensitivity of approximately 91% compared to the Watch-PAT 200 sensitivity of 92% when looking at home PM. However, the Apnealink had an 18% higher specificity compared to the Watch-PAT 200 at AHI ≥ 15. Conclusion: In developing the ideal home-based sleep study for Blacks, the user preference is very important to determine the long-term validity of the device in screening for OSA. Portable devices such as the ApneaLink Plus, which performed as well as PSG and had greater preference can become validated as the go to device when screening for OSA at home. Further studies can determine if self-applying PM devices may provide greater adherence to CPAP device if diagnosed with OSA. Support (If Any): K07AG052685.